Using a hybrid algorithm and active RFID to construct a seamless infant roomingin tracking mechanism. (2015) - Hung, LunPing
Due to the rapid development of sensor and wireless equipment that integrates with information technology to construct intelligent mechanism, the quality of the clinical care of newborn babies has improved. To raise the success rate of requesting roomingin care for newborn babies, babyfriendly hospitals should prevent the mistake of identifying newborns and assure the safety of newborn babies. This paper proposes a mechanism that includes a hybrid algorithm combining Location Fingerprint and Knearest neighbour (KNN) algorithm and active radiofrequency identification technology using received signal strength indication transmission method to build a safer roomingin environment. This mechanism can effectively avoid the situation, such as a stolen or switched baby, and be up to the standard certified by babyfriendly hospital initiative. The nursing department can easily arrange routine nursing works and increase nursing quality. The hospitals benefit from using the system with increased ratio of requesting roomingin care.